1987
DOI: 10.3109/17453678709146340
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hip fracture in Western Sweden 1974-1982: Comparison of rural and urban populations

Abstract: Several epidemiological studies in northern Europe have shown that fractures in the elderly exceed the expected increase in the aging populations. We have compared the incidence of hip fracture in the rural county of Skaraborg and the city of Göteborg in Sweden. After adjustment for age changes in the population, the incidence of hip fracture in Skaraborg County was lower than in Göteborg during the period 1974-1984. The non-age-related increase in the incidence of fractures found in the city was not confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
2
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 15 publications
5
32
2
2
Order By: Relevance
“…Our finding that rural individuals have a greater fracture risk than Hutterites but not nonrural individuals was surprising given previous studies reporting higher fracture rates among individuals residing in rural areas compared with urban areas [2,8,9,11]. Our finding of no population difference in fracture risk when phalangeal and facial fractures were removed suggests that the high fracture rate among rural individuals may be a result of work-related injuries.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Our finding that rural individuals have a greater fracture risk than Hutterites but not nonrural individuals was surprising given previous studies reporting higher fracture rates among individuals residing in rural areas compared with urban areas [2,8,9,11]. Our finding of no population difference in fracture risk when phalangeal and facial fractures were removed suggests that the high fracture rate among rural individuals may be a result of work-related injuries.…”
Section: Discussioncontrasting
confidence: 62%
“…Lifestyle differences, in particular urban versus rural lifestyle, have been implicated previously as a potential risk factor for fractures [2,8]. Previous studies have reported lower fracture risk in elderly rural compared with urban populations in Scandinavia [2,8], Australia [11], and the United States [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective reimbursement aiming at reducing the costs of acute care does not necessarily result in overall savings. In spite of an ever-increasing number of hip fracture patients during recent decades (Zetterberg et al 1985, Mannius et al 1987, the total number of bed-days used for the hip fracture diagnosis in hospitals and after-care facilities has actually decreased (Bauer 1995). However, today's strained economy together with the ongoing dramatic demographic change-an unprecedented increase in the number of old and very old people (The Economist, January 27 1996)-has prompted cut-backs in the health care expenditure.…”
Section: Lars Stromberg Gunnar Ohlen and Olle Svenssonmentioning
confidence: 99%
“…Alffram (1964), Liithje (1983) and Zetterberg et al (1984) noted that the age-specific women/men ratio was higher in cervical than in trochanteric fractures; Alffram remarked that this "might indicate a sexlinked difference between the two types of fractures". Indeed, the sex difference in the incidence of cervical/trochanteric fracture (Cfl) had already been noted by Johansson (1934) and several authors have found that this ratio changes with age, more in women than in men (Jensen 1980, Zetterberg et al 1984, Falch et al 1985, Mannius et al 1987, Sembo et al 1988, Caniggia and Moneale 1989, Jamlo et al 1989). Realizing that "a clear understanding of fracture heterogeneity might lead to new hypotheses concerning etiology" (Melton and Cummings 1987), we report an analysis of the Cfl ratio based on 15 published studies and our own data.…”
mentioning
confidence: 99%